2008
DOI: 10.1021/jp710750f
|View full text |Cite
|
Sign up to set email alerts
|

Rate Constants for 1,5- and 1,6-Hydrogen Atom Transfer Reactions of Mono-, Di-, and Tri-aryl-substituted Donors, Models for Hydrogen Atom Transfers in Polyunsaturated Fatty Acid Radicals

Abstract: Rate constants for 1,5- and 1,6-hydrogen atom transfer reactions in models of polyunsaturated fatty acid radicals were measured via laser flash photolysis methods. Photolyses of PTOC (pyridine-2-thioneoxycarbonyl) ester derivatives of carboxylic acids gave primary alkyl radicals that reacted by 1,5-hydrogen transfer from mono-, di-, and tri-aryl-substituted positions or 1,6-hydrogen transfer from di- and tri-aryl-substituted positions to give UV-detectable products. Rate constants for reactions in acetonitrile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…A few rate constants for unequivocal or competitive intra-HAT processes are given in Figure 1. [14][15][16] These data are representative of a few situations in which 1,n-HAT are enthalpically 3.1. 1,4-HAT in sterically constrained systems Reactions involving 1,4-translocations on a preparative scale are rather scarce; they are often mentioned as unexpected side processes.…”
Section: Theoretical Background and Kinetic Datamentioning
confidence: 88%
See 1 more Smart Citation
“…A few rate constants for unequivocal or competitive intra-HAT processes are given in Figure 1. [14][15][16] These data are representative of a few situations in which 1,n-HAT are enthalpically 3.1. 1,4-HAT in sterically constrained systems Reactions involving 1,4-translocations on a preparative scale are rather scarce; they are often mentioned as unexpected side processes.…”
Section: Theoretical Background and Kinetic Datamentioning
confidence: 88%
“…A few rate constants for unequivocal or competitive intra‐HAT processes are given in Figure 1 1416. These data are representative of a few situations in which 1, n ‐HAT are enthalpically favored.…”
Section: Theoretical Background and Kinetic Datamentioning
confidence: 95%
“…If the corresponding over-the-barrier KIEs at 232.5 and 298 K are near their typical values of 8 and 5, 10c,11 then estimated k H / k D ≈ 3200 and 170 (Table S14, SI) are not far off from the experimental values k H / k D of 1380 and 156 (Table S11 and Figure S2, SI). 35 …”
mentioning
confidence: 94%
“…We prepared radical 1 -H and found that it had a short half-life, τ 1/2 ~ 1 min, at 298 K. We suspected that an intramolecular 1,5-hydrogen atom transfer (1,5-HAT) 911 from the -CH 2 -O- fragment 12,13 might be the factor in the short half-life of 1- H . We investigated the D 8 -isotopomer 1 -D and found that it had a much longer half-life, τ 1/2 > 1 h, with extremely large room-temperature kinetic isotope effect (KIE), e.g., k H / k D ≈ 150 in acetone.…”
mentioning
confidence: 99%
“…The pseudo‐first‐order rate constant for the reaction of THF with radical 8 at ambient temperature is in the order of 10 3 s –1 as explained above. Rates of radical/radical reactions and reactions of radicals with residual oxygen in the LFP studies have pseudo‐first‐order rate constants in the order of 10 4 s –1 at most 21. Thus, any interfering radical reaction was expected to be too slow to be important in the kinetic measurement.…”
Section: Resultsmentioning
confidence: 99%